A Comparative Study on Total Harmonic Distortion of Interleaved Boost Rectifier with the other Boost Derived Topologies - Gollapudi, Srikanth; Lalitanand, G V S N; Ezhilarasi, Angeline (International Journal of Engineering and Technology, 2018)
Boost rectifiers find their applications in the active power factor correction and have been subject to extensive research. Further, various topologies have been introduced, studied and applied in order to make boost rectifiers more and more efficient and better. Accordingly, Bridgeless configuration and Interleaved topology are most popular among others. In this paper, a comparative study between Basic boost rectifier, bridgeless boost rectifier, interleaved boost rectifier and bridgeless interleaved boost rectifier model has been carried out. The differences analyzed are summarized to learn about the best configuration and which can be implemented. Bridgeless configuration reduces conduction losses in the system by removing one diode from line conduction path while two parallel boost converters with anti-phase conduction in a 2-interleaved topology reduces the current ripple. BLIL combines the advantages of both the system in a single circuit.